Ropivacaine preperitoneal wound infusion for pain relief and prevention of incisional hyperalgesia after laparoscopic colorectal surgery: a randomized, triple‐arm, double‐blind controlled evaluation vs intravenous lidocaine infusion, the CATCH study. (3rd June 2018) - Beaussier, M.; Parc, Y.; Guechot, J.; Cachanado, M.; Rousseau, A.; Lescot, T.; ,
Abstract: Aim: The abdominal incision for specimen extraction could trigger postoperative pain after laparoscopic colorectal resections (LCRs). Continuous wound infusion (CWI) of ropivacaine may be a valuable option for postoperative analgesia. This study was undertaken to evaluate the potential benefits of ropivacaine CWI on pain relief, metabolic stress reaction, prevention of wound hyperalgesia and residual incisional pain after LCR. A subgroup with intravenous lidocaine infusion (IVL) was added to discriminate between the peripheral and systemic effects of local anaesthetic infusions. Method: Patients were randomly allocated to three subgroups: CWI (0.2% ropivacaine 10 ml/h for 48 h); IVL (lidocaine 1.5% at 4 ml/h for 48 h); control group. Results: In all, 95 patients were randomized (86 patients analysed). Postoperative pain intensity did not differ significantly between groups. Within the first 24 h after surgery, morphine requirement was significantly lower in the CWI group compared with the IVL group, but there was no significant difference compared with the control group ( P  =   0.02 and P  =   0.15, respectively). The area of hyperalgesia did not differ significantly between subgroups, nor did the hyperalgesia ratio which was 1.2 cm (0.0−6.7) vs 1.9 cm (0.4−4.0) vs 2.0 cm (0.5−7.0) in the CWI, IVL and control groups respectively ( P  =   0.35). The number of patients reporting residual incisional pain after 3 months (3/26 vs 4/23 vs 4/23 in the CWI, IVL and control groups respectively) did not differ significantly between the groups, nor did their metabolic stress reactions. Conclusion: Ropivacaine CWI at the site of the abdominal incision did not provide any significant benefit either on analgesia or on the prevention of wound hyperalgesia after LCR.